2011
DOI: 10.1159/000324341
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Estimate Total Entry to Hard Drug Use: The Case of Intravenous Drug Use in Norway

Abstract: Background/Aims: Epidemiological measures such as the prevalence and incidence of hard drug use are important tools for evaluating drug situations and drug policies. Models for drug use trajectories illustrate how temporary and lasting cessation of and relapse into hard drug use are other important elements in the overall picture of change in hard drug use over time. Estimating the total entry to hard drug use broadens the knowledge of the change in such use. Methods: The entry rate for hard drug use is define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…As such studies are not available in Spain, we considered yearly cessation rates from a thorough review which reported a range of 0.02-0.04 [25]. Our analyses considered these two extreme values.…”
Section: Methodsmentioning
confidence: 99%
“…As such studies are not available in Spain, we considered yearly cessation rates from a thorough review which reported a range of 0.02-0.04 [25]. Our analyses considered these two extreme values.…”
Section: Methodsmentioning
confidence: 99%
“…Further research should also investigate more dynamic ways to describe PDU and integrate recent findings on entry and cessation rates applied to hard drug use [36] as well as the possible associations between indirect trend indicators (e.g. drug-related mortality, seizures, service usage, treatment demand) and the prevalence of drug misuse in a longitudinal perspective in order to fine-tune, complement and further validate nationally applied prevalence estimations of drug misuse and thus contribute to enhance evidence based drug policy planning.…”
Section: Discussionmentioning
confidence: 99%
“…Injecting drug use and needle sharing is the major driver of HCV incidence; 8 however, the coverage of preventive interventions, such as needle and syringe programmes, remains poor among PWIDs. 9 Number of people who actively inject drugs in Norway have been stable at around 9000 since 2012 till 2017 (2.6 per 1000 inhabitants aged 15–64 years), 10 11 and opioids and amphetamines are the main injected drugs. 11 12 Modelling studies suggest that around 7000 former and current PWIDs are living with chronic HCV with an estimated 400 new cases annually in the same time period.…”
Section: Introductionmentioning
confidence: 99%